Internet, adjustment of firms and the spatial division of labour - Claus-Friedrich Laaser; Rüdiger Soltwedel (European Regional Science Association (ERSA), 2002)
The rise of the Internet has been heralded as the 'death of distance' that may eventually entail a 'decline of the city'. Whether or not these futuristic visions will materialize will depend upon how firms and industries react to the Internet as a general-purpose technology. Besides the locational choice of New Economy firms themselves it is the adoption of E-commerce in industries of the 'old' economy which has the potential for re-shaping the economic geography of regions, and which may, in many instances radically so, change the way to manage the internal organization of firms as well as relationships with business partners (B2B) and with consumers (B2C). The paper aims at discussing elements of a conceptual approach for evaluating these spatial effects of E-commerce activities on locational patterns in the old economy by identifying suitable proxy indicators from existing evidence, such as connectivity to IT-infrastructures, sectoral differences in B2B solutions, market (de-)concentration processes, or changes of functional employment structures of cities. Key words: Internet, E-commerce, Organizational Change, Firm Location, Spatial Division of Labour
Keywords: 330